Viral Ubiquitin Ligase Stimulates Selective Host MicroRNA Expression by Targeting ZEB Transcriptional Repressors - Lutz, Gabriel; Jurak, Igor; Kim, Eui Tae; Kim, Ju Youn; Hackenberg, Michael; Leader, Andrew; Stoller, Michelle L.; Fekete, Donna M.; Weitzman, Matthew D.; Coen, Donald M.; Wilson, Angus C. (Viruses, 2017)
Infection with herpes simplex virus-1 (HSV-1) brings numerous changes in cellular gene expression. Levels of most host mRNAs are reduced, limiting synthesis of host proteins, especially those involved in antiviral defenses. The impact of HSV-1 on host microRNAs (miRNAs), an extensive network of short non-coding RNAs that regulate mRNA stability/translation, remains largely unexplored. Here we show that transcription of the miR-183 cluster (miR-183, miR-96, and miR-182) is selectively induced by HSV-1 during productive infection of primary fibroblasts and neurons. ICP0, a viral E3 ubiquitin ligase expressed as an immediate-early protein, is both necessary and sufficient for this induction. Nuclear exclusion of ICP0 or removal of the RING (really interesting new gene) finger domain that is required for E3 ligase activity prevents induction. ICP0 promotes the degradation of numerous host proteins and for the most part, the downstream consequences are unknown. Induction of the miR-183 cluster can be mimicked by depletion of host transcriptional repressors zinc finger E-box binding homeobox 1 (ZEB1)/-crystallin enhancer binding factor 1 (δEF1) and zinc finger E-box binding homeobox 2 (ZEB2)/Smad-interacting protein 1 (SIP1), which we establish as new substrates for ICP0-mediated degradation. Thus, HSV-1 selectively stimulates expression of the miR-183 cluster by ICP0-mediated degradation of ZEB transcriptional repressors.